Pengaruh Pemberian Pelatihan Pengembangan Diri terhadap Loyalitas Anggota di Formasi Ar-Ruuh UMA - Ihsan Habib Siregar; Hairul Anwar Dalimunthe (Faculty of Psychology, Universitas Medan Area, 2018)
This study aims to see the influence of self-development training to member loyalty. Research subjects are 40 members of Formasi Ar-Ruuh UMA. The samples were divided into experimental groups (Trained) and control groups (No training). Using 50 instruments of loyalty as a measuring instrument. Data analysis techniques using Wilcoxon Test, with the following results: 1. There’s influence of training on experimental group, significance coefficient 0.005. p 0.005 <0.05, hypothesis is accepted. 2. There’s no significant increase in the control group. p = 0,513. p 0,513> 0,05, hypothesis is rejected. 3. There’s no significant difference between the two groups, p = 0.225. p 0.225> 0.05, hypothesis is rejected. The experimental group further increased its loyalty score by a pretest average of 125.85, the posttest rising to 130.25. The control group obtained a pretest average of 124.75, the posttest rising to 125.00. Self-development training affects loyalty improvement with pretest empirical mean experimental group 125,85, pretest control group 124,75, posttest experimental group 130,25, posttest control group 125,00. The empirical average value is greater than the hypothetical value (100) and the difference over the SD number is 11.440, 16.227, 5.447, 16.387.